Influence of fungal decay on mechanical properties of bio-based sheet molding compounds (SMC). (5th December 2022) - Gortner, Florian; Schüffler, Anja; Fischer-Schuch, Jochen; Mitschang, Peter; Bachmann, Paula
Sheet Molding Compound (SMC) was initially developed in the 1960s and enabled for the first time the production of glass fiber reinforced polymer composite in mass scale production and at an advantageous price. Today, material and process are well established for the production of semi-structural and structural components in various applications such as construction industry, aircraft applications and automotive components. Based on increasing ecological and economical requirements for construction materials a newly and largely bio-based SMC semi-finished material was developed. This paper shows the ability using bio-based components to replace crude oil and mineral based components in SMC. Therefore, test methods for shelf life and fungal decay tests were developed to prove that there is no influence to mechanical properties of the bio-based specimens. The different test series showed that there is a bigger influence of sample preparation for shelf life tests than from fungal decay to the specimens.